2013
DOI: 10.4103/2231-4040.107495
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles laden in situ gelling system for ocular drug targeting

Abstract: Designing an ophthalmic drug delivery system is one of the most difficult challenges for the researchers. The anatomy and physiology of eye create barriers like blinking which leads to the poor retention time and penetration of drug moiety. Some conventional ocular drug delivery systems show shortcomings such as enhanced pre-corneal elimination, high variability in efficiency, and blurred vision. To overcome these problems, several novel drug delivery systems such as liposomes, nanoparticles, hydrogels, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…The in vitro release data revealed the slow release of LF from nanosuspension formulations for more than 8 h. The highest release percentage was obtained from formula C1 which [43][44][45][46]. It was also observed that formulations containing TPP as the crosslinker showed higher release percentages compared to Fig.…”
Section: In Vitro Release Studiesmentioning
confidence: 66%
“…The in vitro release data revealed the slow release of LF from nanosuspension formulations for more than 8 h. The highest release percentage was obtained from formula C1 which [43][44][45][46]. It was also observed that formulations containing TPP as the crosslinker showed higher release percentages compared to Fig.…”
Section: In Vitro Release Studiesmentioning
confidence: 66%
“…It is known as 'nanoparticle laden in situ gel'. In an extensive review, Kumar et al have described every aspect of this novel formulation [75]. The polymeric nanoparticle-loaded in situ gel provides a sustained and prolonged release.…”
Section: Recent Advances In Ophthalmic Nanoparticulate Drug Delivery mentioning
confidence: 99%
“…These in situ activated gel-forming systems seem to be favoured as they can be administered in a drop form and produce considerably less blurred vision. Owing to its control of drug release, the dosage form is more acceptable by the patients and thus increases the patient compliance [75].…”
Section: Recent Advances In Ophthalmic Nanoparticulate Drug Delivery mentioning
confidence: 99%
“…At specific pH there is Electrostatic, hydrophobic interaction and Hydrogen bonding takes place, hence leads to inter-diffusion and a conformational change in the polymer results in its swelling. Hence sol to gel transition is pH triggered [30]. Figure 1 shows the in situ gelling phenomena by pH modification of the system.…”
Section: According To Physiological Mechanisms Causing Gelation Of Pomentioning
confidence: 99%
“…It is also called osmotically induced gelation. Ion sensitive polymers are able to crosslink with cations (monovalent, divalant) present in lacrimal fluid on ocular surface and enhance the retention time of drug [30].…”
Section: Poly (N-isopropylacrylamide)mentioning
confidence: 99%